Tension Lap Splice Length of Reinforcing Bars Embedded in Reactive Powder Concrete (RPC). (June 2019) - Al-Quraishi, Hussein; Al-Farttoosi, Mahdi; AbdulKhudhur, Raad
Abstract: Reactive Powder Concrete (RPC) is an emerging cementations construction material which has superior mechanical properties such as high compressive and tensile strength, high density and homogeneous. In this research, the tension splice behaviour of reinforcement bars embedded in RPC was investigated using experimental and numerical studies. Six reinforced RPC beams with four-point loading were tested. The parameters investigated in the experimental program were steel fibre contents, size of reinforcing bar, tension reinforcement splice length, and amount of transverse reinforcement. The experimental findings showed that the increasing of steel fibre content, amount of transverse reinforcement, length of spliced bars, and diameter of spliced bars increased the tension splice strength of steel bras embedded in RPC members. Splitting of concrete is the dominate mode of failure that occurred in RPC beams spliced with tension reinforcement. Finite element method was used in this study to simulate the behaviour of members tested experimentally and a comparison between experimental and numerical results was conducted. The comparisons showed a good agreement between experimental results and numerical results in terms of load deflection curves and splice strengths. The verified finite element model was used then to study the effect of wide range of data for variables affect the splice strength using a parametric study. A proposed design equation of splice strength of tension reinforcing bars embedded in RPC was proposed in this study and verified with numerical results.